KINERJA SERAT KAWAT BENDRAT SEBAGAI BAHAN TAMBAH BETON FAS 0.4 - Lantif Anggrahita Pratama; Ahmad Hakam Rifqi; Muhtarom Riyadi (Politeknik Negeri Jakarta, 2021)
Concrete is the most important part of a construction building. The purpose of this study was to examine how the comparison of physical and mechanical properties and optimum levels of the addition of straight tie wire as an added material with a water-cement ratio of 0.4. The percentage of addition of straight tie wire: 0%, 0.5%, 0.75%, 1.0%, of the total weight of the specimen with a tie-wire length of 8 cm. The test specimens for compressive strength, modulus of elasticity, and split tensile are in the form of a cylinder with a diameter of 15 cm and a height of 30 cm, and the specimen for flexural strength is a block with a length of 50 cm, a width of 10 cm and a height of 10 cm. The results show that the maximum compressive strength test on tie wire occurred at a percentage of 0.75% of 16.56 MPa. The maximum modulus of elasticity in tie wire occurred at a percentage of 0.75% of 15184.56 MPa. The maximum split tensile strength of tie wire occurred in a percentage of 0.75% of 1.165 MPa, and the maximum flexural strength of tie wire occurs at a percentage of 0.75% of 1.950 MPa. The research results concluded that the addition of a straight tie-wire to the concrete mixture could increase the compressive strength, split tensile strength, tensile strength, and elastic modulus of concrete. Keywords: Compressive Strength, Tensile Strength, Flexural Strength, Modulus Elasticity.